Bacterial CagA protein induces degradation of p53 protein in a p14ARF-dependent manner. Issue 7 (30th July 2014) - Wei, Jinxiong; Noto, Jennifer M; Zaika, Elena; Romero-Gallo, Judith; Piazuelo, Maria Blanca; Schneider, Barbara; El-Rifai, Wael; Correa, Pelayo; Peek, Richard M; Zaika, Alexander I
Abstract : Objective: Infection with Helicobacter pylori is the strongest known risk factor for adenocarcinoma of the stomach. Tumorigenic transformation of gastric epithelium induced by H. pylori is a highly complex process driven by an active interplay between bacterial virulence and host factors, many aspects of which remain obscure. In this work, we investigated the degradation of p53 tumour suppressor induced by H. pylori . Design: Expression of p53 protein in gastric biopsies was assessed by immunohistochemistry. Gastric cells were co-cultured with H. pylori strains isolated from high-gastric risk and low-gastric risk areas and assessed for expression of p53, p14ARF and cytotoxin-associated gene A (CagA) by immunoblotting. siRNA was used to inhibit activities of ARF-BP1 and Human Double Minute 2 (HDM2) proteins. Results: Our analysis demonstrated that H. pylori strains expressing high levels of CagA virulence factor and associated with a higher gastric cancer risk more strongly suppress p53 compared with low-risk strains in vivo and in vitro . We found that degradation of p53 induced by bacterial CagA protein is mediated by host HDM2 and ARF-BP1 E3 ubiquitin ligases, while the p14ARF protein counteracts H. pylori- induced signalling. Conclusions: Our results provide novel evidence that tumorigenicity associated with H. pylori infection is linked to inhibition of p53 protein by CagA. We propose a model in which CagA-induced degradation of p53 protein is determined by a relative level of p14ARF. In cells in which p14ARF levels were decreased due to hypermethylation or deletion of the p14ARF gene, H. pylori efficiently degraded p53, whereas p53 is protected in cells expressing high levels of p14ARF.